ENGLISH FOREIGN LANGUAGE DIGITAL LITERACY AT PESANTREN BASED SCHOOL IN INDONESIA: A SYSTEMATIC RESEARCH REVIEW - Wardah An Nuriyah; Nur Afifi (IKIP Siliwangi, 2023)
The advancement of information and communication technology has been greeted favorably by various elements in Indonesian education, including Pesantren with the aim of instilling the concept of digital literacy for students. This study uses a systematic review, namely the research process by identifying previous research with systematic analysis methods by identifying literature in the form of journal articles obtained from Google Scholar. This method has been used to provide in-depth research and perform basic analysis, assess and synthesize complex thoughts to draw conclusions from the results of analysis of literature data, and answer problems efficiently, clearly, and relevantly. From the results of a review of several journal articles, it can be seen that most of the modern pesantren-based Islamic boarding schools have received fairly good digital literacy education. Digital support and facilities have also been provided. However, they also have problems with timing, individual digital skills, and an unstable curriculum. Regarding the review of the English learning process, the provision of digital training for students needs to be improved. Even though there are many challenges, students must be ready to implement them, so they are not left behind by increasingly sophisticated technological advances.Â Keywords:Â EFL; Digital Literacy; Pesantren